Design of an original thermoelectric generator prototype with heat pipe - Kalaichelvam Ramdass (2019)
Depletion rate of fossil fuel is high for both energy generation and consumption purpose. Thus, the emission of harmful greenhouse gases can be reduced through by the means of investing heavily in renewable energy sources. In recent years, industries around the world produce large amount of waste heat that were released to the surroundings and were unable to recycle them. Many industries are looking for possible solutions to fully utilize the production of waste heat and converting them to useful form of energy sources for power generation, mainly electricity. This could possibly be done by utilizing Thermoelectric Generator (TEG) in recovering waste heat and generating electricity.